(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Natural disasters are a common phenomenon in every country in the world. However, the differences between the impact on the devastation and victims depend on how the disaster is managed and how well preparedness is arranged by the agency responsible for dealing with disaster in helping the affected victims, either natural or unnatural disaster. Good disaster management will consider the authorities’ functions until they had a good perception from the community or society. This study examines the relationship between policy, planning, risk analysis, and data management on disaster preparedness of Infantry Battalion personnel in the State of Kelantan in the 8th Infantry Brigade. The quantitative research method by distributing questionnaires was used to obtain feedback on 297 respondents who were sampled for this study. This study uses a questionnaire that contains several questions on policy, planning, risk management, data management, communication, and disaster preparedness. The data were analysed using Statistical Package for Social Science (SPSS) version 25 and Partial Least Squares (PLS) version 3.2.8. The dependent variables are the disaster preparedness of Infantry Battalion personnel in the 8th Infantry Brigade, while the independent variables are the policy, planning, risk analysis, and data management. The study’s findings showed a significant relationship between all the independent variables on the disaster preparedness of the Eighth Brigade personnel. In such cases, it is recommended that the Malaysian Army should scrutinize and focus on exposure to all levels in the battalion regarding disaster management. Proposed approaches and improvements and confidence in performing and handling tasks are highly dependent on the experience and knowledge of personnel either formally or informally. Personnel who received more analysed exposure were more confident and contributed to the effectiveness of actions during the mobilization of disaster operations.